Water-Soluble pillararene-functionalized graphene oxide for in vitro raman and fluorescence dual-mode imaging - Zhao, Yanli (2014)
This study provides a successful preparation of biocompatible hybrid materials (1-GO and 2-GO) by the integration of graphene oxide (GO) with water-soluble pillararenes (bolaamphiphile 1 and tadpolelike amphiphile 2) for dual-mode Raman and fluorescence bioimaging in vitro. The investigations show that pillararenes 1 and 2 were loaded onto the surface of GO through strong hydrogen-bonding interactions. Aqueous suspensions of 1-GO and 2-GO are stable and can be kept for a long time. After confirming their good biocompatibility by using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay, the 1-GO and 2-GO hybrids were endocytosed by HeLa cells for in vitro Raman imaging. It was found that 1-GO presents better Raman imaging than 2-GO. When a fluorescent guest molecule, bipyridinium derivative 3, was added into the suspensions of the hybrids, the suspensions of 1-GO and 2-GO were as stable as the original. The suspensions of the inclusion complexes (1-GO[DOT OPERATOR]3 and 2-GO[DOT OPERATOR]3) formed from 1-GO and 2-GO with 3 can also be endocytosed by HeLa cells to enable in vitro fluorescence imaging to be performed. It was found that 1-GO[DOT OPERATOR]3 performs better than 2-GO[DOT OPERATOR]3. The current research has determined the capacities of pillararene-modified GO for combined bioimaging, which paves the way for using these biocompatible materials towards dual-mode diagnostics.